FACTORS AFFECTING RECURRENT UTIS IN POST-MENOPAUSAL WOMAN-A SINGLE CENTER, TERTIARY CARE STUDY (The Research of Medical Science Review, 2025)
Background: Recurrent urinary tract infections (UTIs) are a common urological concern among postmenopausal women. Identifying risk factors associated with recurrent UTIs can help guide preventive strategies and tailored management. Objective: To evaluate the frequency of recurrent UTIs in postmenopausal women and compare associated risk factors including age, duration of menopause, diabetes, hormone replacement therapy (HRT) use, genitourinary (GU) instrumentation, and body mass index (BMI). Study Design and Setting: This prospective observational study was conducted at the Department of Renal Transplant Surgery & Urology, PAF Hospital E-9, Islamabad from 25 -11-2024 to 25-04-2025. Methodology: Postmenopausal women presenting with urological complaints were enrolled. Patients with anatomical abnormalities, genitourinary fistulas, malignancies, or stones were excluded. Data collected included age, duration of menopause, diabetes, HRT usage, BMI, and history of GU instrumentation. Patients were categorized into two groups: Group A (with recurrent UTIs) and Group B (without). Statistical analysis was performed using SPSS version 23. Chi-square and t-tests were used, with p < 0.05 considered significant. Results: A total of 135 women were included, with a mean age of 62.63 ± 13.45 years. Recurrent UTIs were present in 45 (33.3%). GU instrumentation was significantly more frequent in Group A (62.2%) compared to Group B (32.2%) (p = 0.00). No significant differences were observed in age, menopause duration, diabetes, HRT use, or BMI between groups. Conclusion: GU instrumentation is significantly associated with recurrent UTIs in postmenopausal women. Other factors such as age, diabetes, and HRT use showed no significant association.